Visual, tactile and auditory memory: any difference between students? - Ling, Leh Qing; Wong, Kellin Kai Xin; Lim, Chin Fen; Treshia Tapui; Toh, Bing Zhao; Chua, Bee Seok (Unit Penyelidikan Psikologi dan Kesihatan Sosial UMS, 2019)
To recall objects depends on how we receive information in our daily life. There is three-way to receive information: hear, see or touch. Each way reacts differently to memory performance. Thus, the main purpose of this study is to investigate the differences between auditory, visual and tactile information in the memory performance. Besides, this study also aimed to find out the differences between gender and field of study in their memory performance. A total of 60 sciences and social sciences students in university (30 females and 30 males) involved in this study. The tool to record the memory performance was namely A Message from Your Brain. The result has shown that visual and tactile information were more efficient than auditory information in the memory performance. The finding also shows there was a significant difference between male and female students in auditory memory. Females were outperformed in auditory memory performance compared to males. The result also shows that there was a significant difference between science students and social sciences students on visual memory performance. Students from the sciences field have better performance in visual and tactile memory than social sciences students.